2019
DOI: 10.1002/aoc.5257
|View full text |Cite
|
Sign up to set email alerts
|

Bithiophene triarylborane dyad: An efficient material for the selective detection of CN and F ions

Abstract: A new fluorescent chemosensor based on bithiophene coupled dimesitylborane (BMB‐1) was synthesized and characterized. BMB‐1 was used for colorimetric and turn‐on fluorescent sensing of cyanide (CN−) and fluoride (F−) ions, in the presence of other competitive anions in an aqueous (CH3CN–H2O) medium. BMB‐1 showed a hypsochromic shift (blue shift) with addition of CN− and F− ions in absorption studies. The lower detection level of CN− and F− ions is 1.37 × 10−9 and 1.75 × 10−9 M, respectively. The BMB‐1 binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…leads to almost complete quenching (≈90 %) of the initial emission peaks (340 nm and 470 nm, respectively) for both BDT 1 derivatives. Absorption and fluorescence titration experiments revealed that both mono‐ and bis‐borylated benzodithiophenes have a great response to the addition of fluorides, according to what had been reported for similar dimesitylboryl‐functionalized scaffolds [11b,19] . These results indicate that compound 1 and 2 are promising scaffolds for applications as building blocks for fluoride‐detecting turn‐off sensor materials.…”
Section: Resultssupporting
confidence: 71%
“…leads to almost complete quenching (≈90 %) of the initial emission peaks (340 nm and 470 nm, respectively) for both BDT 1 derivatives. Absorption and fluorescence titration experiments revealed that both mono‐ and bis‐borylated benzodithiophenes have a great response to the addition of fluorides, according to what had been reported for similar dimesitylboryl‐functionalized scaffolds [11b,19] . These results indicate that compound 1 and 2 are promising scaffolds for applications as building blocks for fluoride‐detecting turn‐off sensor materials.…”
Section: Resultssupporting
confidence: 71%
“…2(a)). 7 Upon changing the heteroatom from –PPh 2 ( 6 ) (332 nm, DMF) to S( 7 ) to Se ( 8 ) (332 nm, CH 3 CN) no considerable change was observed in their absorbance maxima (Fig. 2(a)).…”
Section: Resultsmentioning
confidence: 99%
“…The bond distances of B–F in 8 -[F], 9 -[F], and 11 -[F] are 1.482(2) Å, 1.470(8) Å, and 1.462(4) Å, respectively, and the B–C (B–CN) bond distance in 7 -[CN] and 8 -[CN] are 1.634(3) Å and 1.623(7) Å respectively, which are typical of that obtained in other fluoroborates and cyanoborates such as [Ph 3 BCN] − (1.65 Å). 7,14…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At this standpoint, highly popular approaches such as multiple hydrogen bonding, anion-π, and supramolecular electrostatic interactions have been frequently used for the instantaneous fluorometric recognition [34][35][36]. In this sense, such macrocyclic compounds based on various classic skeletons such as crown ethers, cyclodextrins, cucurbiturils, and pillararenes have been often employed as receptors for anion sensing due to leading to a wider detection range, lower detection limit, and excellent ability to prevent interferences against coexisting ions [37][38][39][40].…”
mentioning
confidence: 99%